DILEMA PERLINDUNGAN PENGETAHUAN TRADISIONAL BERBASISKAN HAK KEKAYAAN INTELEKTUAL PADA SENI UKIRAN MINANGKABAU - Surya Prahara; Mayuasti Mayuasti; Deswita Rosra; Dwi Astuti Palupi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Traditional knowledge is an issue that has been discussed in national and international conference. The current issue is the protection of traditional knowledge in Indonesia in the concept of Intellectual Property Right. The protection of traditional knowledge in Minangkabau craft based on Intellectual Property Right is the problem that is elaborated in this article. Normative legal design is the research design used to answer the research’s problem. The data are collected from the secondary data and literature study. The results of this research show that the concepts of IPR are contrary to the principles of traditional knowledge. Traditional knowledge is originally from indigenous communities that are communal, whereas IPR does not approve it. Hence, the existing law has not provided legal certainty and benefit optimally in protecting traditional knowledge. The solution of this problem is IPR Law must be renewed and a sui generis law regarding to traditional knowledge has to be constructed. It must be clear that local people are declared and certified as the owner of traditional knowledge based on Intellectual Property Right. The recognition of traditional knowledge based on IPR must be communal and non-profit oriented, so it can be owned by all indigenous people.Keywords: Law inforcement, intelectual propertyright, traditional knowledge, minangkabau craft